Two-Dimensional Lattice Boltzmann Model for Droplet Impingement and Breakup in Low Density Ratio Liquids (Communications in Computational Physics, 2011)
A two-dimensional lattice Boltzmann model has been employed to simulatethe impingement of a liquid drop on a dry surface. For a range of Weber number,Reynolds number and low density ratios, multiple phases leading to breakup havebeen obtained. An analytical solution for breakup as function of Reynolds and Webernumber based on the conservation of energy is shown to match well with the simulations.At the moment breakup occurs, the spread diameter is maximum; it increaseswith Weber number and reaches an asymptotic value at a density ratio of 10. Dropletbreakup is found to be more viable for the case when the wall is non-wetting or neutralas compared to a wetting surface. Upon breakup, the distance between the daughterdroplets is much higher for the case with a non-wetting wall, which illustrates the roleof the surface interactions in the outcome of the impact.